Bithyniid snails (Gastropoda: Bithyniidae) infected with Xiphidiocercariae in Thailand include a new record of Bithynia siamensis siamensis as the intermediate host of Plagiorchis and Paralecithodendrium. - Abdulhakam Dumidae; Jiranun Ardpairin; Supawan Pansri; Chanatinat Homkaew; Mayura Nichitcharoen; Aunchalee Thanwisai; Apichat Vitta (PLoS ONE)
Bithyniids are freshwater snails that play a crucial role in the transmission of various parasitic trematodes of medical and veterinary importance. In this study, we explored the prevalence of cercarial trematode infections in bithyniid snails from Thailand and examined the species diversity of both the intermediate snail hosts and parasite larvae. A total of 688 bithyniid snails were collected from diverse natural habitats at 24 locations in 16 provinces across 5 regions of Thailand. The presence of larval trematode infections was examined using the cercarial shedding method. Both the collected snails and the emerging cercariae were identified at the species level using a combination of morphological and molecular techniques. The mitochondrial COI and 16S rDNA sequences of bithyniid snails, along with the ITS2 sequences of cercariae, were obtained via PCR amplification and sequencing. Three species of bithyniid snails were identified in this study: Bithynia funiculata, Bithynia siamensis siamensis, and Hydrobioides nassa. Among these species, B. s. siamensis exhibited the highest population density, followed by B. funiculata and H. nassa. The overall rate of cercarial infection in the bithyniid snails was relatively low, at 1.45%. H. nassa snails had the highest infection prevalence, at 11.11%, while B. s. siamensis had a prevalence of 1.39%. Only the morphological type of the xiphidiocercariae was detected. BLASTn searches in GenBank and phylogenetic trees based on xiphidiocercariae were used to classify the samples into four different families spanning two superfamilies of digenean trematodes. The genera Plagiorchis, Prosthogonimus, Paralecithodendrium, and cercaria of Renicolidae are reported for the first time in B. s. siamensis. Plagiorchis and Paralecithodendrium are significant genera of zoonotic trematodes. These findings indicate that B. s. siamensis and H. nassa can act as the first intermediate hosts for various parasitic trematodes in Thailand.